The Survey of Knowledge, Attitude and Performance Of Female Barbers in Relation to Job's Environmental Health: A Case Study of Malayer City - Ali Almasi; Mitra Mohamadi; Mohsen Poursadeghiyan; Yonwa Sohrabi; Samira Mohamadi; Masoome Komijani (Iranian Journal of Health, Safety and Environment, 2016)
Hygiene disregarding and usage of contaminated tools leads to viral infections, fungal, bacterial and skin diseases, eczema, warts, tetanus and so on. Thus assessment of knowledge, attitudes and performance of barbers in order to ensure the security and public health is really necessary. This study is aimed at determining the knowledge, attitude and performance of female barbers in relation to job's environmental health in Malayer city. In present descriptive- analytical study, 75 female barbers sampling of Malayer city were selected by clusters - systematic method. The data were obtained through questionnaires for completion and checklist. Data analysis was performed using SPSS 21 statistical software. The result showed, 86.66% of people have attained correct awareness of regulations and 92.28% had positive attitude toward regulations and 86.38% of people in this study showed appropriate health practice. In order to, compare the average knowledge level in regard to parameters such as age, work experiences and income situation showed a statistically significant difference. In attitude and performance section, the difference between age and mentioned parameters was not statistically significant (P≥ 0.05). Despite the desirable level of knowledge, attitude and practice of barbers female in Malayer city, in order to improve the situation, to be better the presence of barbers in special guilds courses to train seriously.